Structural timber design to Eurocode 5 - Porteous, Jack (Wiley-Blackwell, 2013)
Structural Timber Design to Eurocode 5 provides practising engineers and specialist contractors with comprehensive, detailed information and in-depth guidance on the design of timber structures based on the common rules and rules for buildings in Eurocode 5 - Part 1-1. It will also be of interest to undergraduate and postgraduate students of civil and structural engineering. It provides a step-by-step approach to the design of all of the commonly used timber elements and connections using solid timber, glued laminated timber or wood based structural products, and incorporates t.